2000
DOI: 10.1074/jbc.m001475200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Caspase Cleavage of Huntingtin Reduces Toxicity and Aggregate Formation in Neuronal and Nonneuronal Cells

Abstract: Huntington's disease is a neurodegenerative disorder caused by CAG expansion that results in expansion of a polyglutamine tract at the extreme N terminus of huntingtin (htt). htt with polyglutamine expansion is proapoptotic in different cell types. Here, we show that caspase inhibitors diminish the toxicity of htt. Additionally, we define htt itself as an important caspase substrate by generating a site-directed htt mutant that is resistant to caspase-3 cleavage at positions 513 and 530 and to caspase-6 cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
253
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(262 citation statements)
references
References 40 publications
8
253
1
Order By: Relevance
“…Cleavage of Htt by caspase-3 yields a 70 kDa (80 kDa; expanded Htt) fragment and 75 kDa (85 kDa; expanded Htt) fragment (sites at D513, D552), while caspase-6 cleavage yields an 80 kDa (90 kDa; expanded Htt) fragment (cleavage site at D586). 36 As shown in Figure 1b,c, caspase-2 is also capable of cleaving Htt to generate a cleavage product at approximately 75 kDa (85 kDa; expanded Htt), which corresponds to cleavage at D552. Comparison of Htt cleavage by caspase-2, -3, and caspase-6 with various caspase-resistant forms of Htt (Figure 1c) demonstrates that caspase-2 cleaves at D552 in Htt3949-138 yielding an 85 kDa cleavage product.…”
Section: Hd Is Specifically Cleaved By Caspase-2 At Caspase Consensusmentioning
confidence: 94%
See 2 more Smart Citations
“…Cleavage of Htt by caspase-3 yields a 70 kDa (80 kDa; expanded Htt) fragment and 75 kDa (85 kDa; expanded Htt) fragment (sites at D513, D552), while caspase-6 cleavage yields an 80 kDa (90 kDa; expanded Htt) fragment (cleavage site at D586). 36 As shown in Figure 1b,c, caspase-2 is also capable of cleaving Htt to generate a cleavage product at approximately 75 kDa (85 kDa; expanded Htt), which corresponds to cleavage at D552. Comparison of Htt cleavage by caspase-2, -3, and caspase-6 with various caspase-resistant forms of Htt (Figure 1c) demonstrates that caspase-2 cleaves at D552 in Htt3949-138 yielding an 85 kDa cleavage product.…”
Section: Hd Is Specifically Cleaved By Caspase-2 At Caspase Consensusmentioning
confidence: 94%
“…[34][35][36] We have previously shown that Htt is cleaved in vitro by caspase-3 at amino acids 513 and 552, and by caspase-6 at amino-acid position 586. 36 However, in vivo, we found that Htt is specifically cleaved at a caspase consensus site at amino acid 552 in pyramidal cortical neurons, while the caspase consensus site at amino acid 513 does not appear to be utilized. 31 Since caspase-3 cleaves at both D513 and D552, we further evaluated the specificity of caspases in cleaving Htt.…”
Section: Hd Is Specifically Cleaved By Caspase-2 At Caspase Consensusmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonpathological length polyglutamine peptides are inherently capable of forming fibrils on their own, albeit slowly (20), yet this behavior generally is not observed in the context of an entire protein. Furthermore, sequences of the regions immediately flanking the polyglutamine tract have been shown to influence the rate of aggregation (52), and some polyglutamine proteins undergo necessary proteolysis prior to aggregation, with the release of a polyglutamine-containing fragment that subsequently forms fibrils (53)(54)(55)(56). Therefore, it is conceivable that domains such as the Josephin domain in ataxin-3 may play a role in maintaining the solubility of the protein, or exert a restraining force such that the conformational shift to the misfolded form is impeded or is energetically less favorable.…”
Section: Kinetic Analysis Of Acid-induced Denaturation Of Ataxin-3-mentioning
confidence: 99%
“…However, upon expansion, the native random coil conformation of the polyglutamine tract becomes a more prominent feature of the overall protein structure, and more importantly, the intrinsic propensity of the polyglutamine tract to adopt an inappropriate conformation may be strengthened, and the counteractive influence of the external regions to this transition may become less effective. Similarly, the disruption of nonpolyglutamine domains and regions under denaturing conditions (24,25) or their removal by cleavage (53)(54)(55)(56) would also result in their loss of ability to prevent the transition to the misfolded conformer.…”
Section: Kinetic Analysis Of Acid-induced Denaturation Of Ataxin-3-mentioning
confidence: 99%